Automated inflammatory bowel disease detection using wearable bowel sound event spotting - Baronetto, Annalisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (Frontiers in Digital Health, 2025)
Introduction: Inflammatory bowel disorders may result in abnormal Bowel Sound (BS) characteristics during auscultation. We employ pattern spotting to detect rare bowel BS events in continuous abdominal recordings using a smart T-shirt with embedded miniaturised microphones. Subsequently, we investigate the clinical relevance of BS spotting in a classification task to distinguish patients diagnosed with inflammatory bowel disease (IBD) and healthy controls. Methods: Abdominal recordings were obtained from 24 patients with IBD with varying disease activity and 21 healthy controls across different digestive phases. In total, approximately 281 h of audio data were inspected by expert raters and thereof 136 h were manually annotated for BS events. A deep-learning-based audio pattern spotting algorithm was trained to retrieve BS events. Subsequently, features were extracted around detected BS events and a Gradient Boosting Classifier was trained to classify patients with IBD vs. healthy controls. We further explored classification window size, feature relevance, and the link between BS-based IBD classification performance and IBD activity. Results: Stratified group K-fold cross-validation experiments yielded a mean area under the receiver operating characteristic curve ≥0.83 regardless of whether BS were manually annotated or detected by the BS spotting algorithm. Discussion: Automated BS retrieval and our BS event classification approach have the potential to support diagnosis and treatment of patients with IBD.
CRIS-Team Scopus Importer:2025-04-11
Keywords: bowel sound; digestion monitoring; inflammatory bowel disease; machine learning; ubiquitous computing

Case report of severe constrictive perimyocarditis and ischemic hepatitis in a Crohn’s disease patient upon infliximab-induced lupus-like syndrome - Hirschmann, Simon; Fischer, Sarah; Klenske, Entcho; Dechant, Katharina; Distler, Jörg; Treutlein, Christoph; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2021)
Anti-tumor necrosis factor (TNF) antibodies have become an indispensable part in the therapeutic landscape of treating inflammatory bowel disease (IBD) patients. Nevertheless, they can be associated with the occurrence of severe systemic side effects. Here, we report the case of a 23-year-old patient with ileocolonic Crohn’s disease in endoscopic remission under ongoing anti-TNF infliximab therapy with occurrence of novel generalized arthralgia, pleuritic chest pain, and dyspnea. Clinical, laboratory, and imaging diagnostic workup in an extended clinical routine setting at the University Hospital of Erlangen, Germany, was used by a multidisciplinary team consisting of gastroenterologists, radiologists, cardiologists, and rheumatologists to investigate the underlying cause of the clinical symptoms in the patient. The results received using the aforementioned diagnostic setup led to the diagnosis of severe constrictive perimyocarditis due to infliximab-induced lupus-like syndrome with distinct ANA reactivity and elevated anti-dsDNA levels. Furthermore, pronounced ischemic hepatitis was diagnosed. Infliximab treatment was immediately stopped, and initiated corticosteroid pulse therapy only led to partial response as it had to be reduced due to pronounced psychiatric side effects. Persistent signs of pericarditis required additional ibuprofen therapy, which led to subsequent resolution of cardial symptoms. Formerly elevated liver enzymes returned to normal, and there were no clinical signs of recurrence of Crohn’s disease activity over 18 months of follow-up. The patient was subsequently switched to ustekinumab therapy for further treatment of underlying Crohn’s disease. This case report describes for the first time severe infliximab-induced lupus-like syndrome in an IBD patient, concurrently mimicking ST-elevation myocardial infarction with MRI visualization of pericarditis, occurrence of ischemic hepatitis, and pronounced signs of systemic inflammation.
CRIS-Team Scopus Importer:2021-10-15
Keywords: anti-TNF antibody; case report; Crohn’s disease; infliximab; lupus-like syndrome

Clinical Pharmacist Counselling Improves Long-term Medication Safety and Patient-reported Outcomes in Anti-TNF-treated Patients With Inflammatory Bowel Diseases: The Prospective, Randomized AdPhaNCED Trial. - Plechschmidt, Johannes; Fietkau, Konstantin; Hepp, Tobias; Dietrich, Peter; Fischer, Sarah; Krebs, Sabine; Neurath, Markus; Dörje, Frank; Atreya, Raja (Inflammatory Bowel Diseases, 2025)
BACKGROUND: Antitumor necrosis factor (anti-TNF) antibody treatment has led to marked improvements in the management of patients with inflammatory bowel diseases (IBDs). Nevertheless, anti-TNF therapy is associated with potential adverse drug reactions (ADRs). Our prospective, randomized trial investigated the effect of intensified clinical pharmacist counselling in a multidisciplinary team on medication safety in anti-TNF-treated IBD patients. METHODS: Patients with IBD with ongoing anti-TNF treatment were enrolled in our tertiary center AdPhaNCED trial and randomized to either receive conventional standard of care (control group) or additional clinical pharmacist counselling (intervention group) over 12 months. The primary end point consisted of the number and severity of ADRs associated with anti-TNF therapy. Secondary end points included patient satisfaction with medication information and medication safety. RESULTS: One hundred twenty-seven IBD patients were included in this study. Anti-TNF-related ADRs were significantly lower in the intervention compared with the control group (0.20 vs 0.32 [mean] ADR/patient/month, P = .006) after 12 months. The risk of more severe ADRs (Common Terminology Criteria for Adverse Events [CTCAE] grade ≥2) was significantly higher in the control compared with the intervention group (hazard ratio, 0.34; P = .001). The probability of ADR resolution (hazard ratio, 2.02; P < .001) and patient satisfaction with medication information (14.82 vs 11.60; P < .001) were significantly higher in the intervention group compared with the control group. CONCLUSIONS: Our study results demonstrate that intensified pharmacist counselling significantly reduces the occurrence and severity of therapy-related ADRs and improves patient satisfaction. Clinical pharmacists should therefore be part of a holistic approach to IBD care delivered by a multidisciplinary team.
EVALuna2:566019
Keywords: inflammatory bowel diseases; patient reported outcomes; adverse drug reaction management; medication safety; patient support program

Intestinal Barrier Healing Is Superior to Endoscopic and Histologic Remission for Predicting Major Adverse Outcomes in Inflammatory Bowel Disease: The Prospective ERIca Trial - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Fischer, Sarah; Waldner, Maximilian; Colombel, Jean Frédéric; Hartmann, Arndt; Neurath, Markus (Gastroenterology, 2023)
Background & Aims: Endoscopic and histologic remission have emerged as key therapeutic goals in the management of inflammatory bowel diseases (IBD) that are associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of barrier healing with endoscopic and histologic remission for predicting long-term disease behavior in a large cohort of patients with IBD in clinical remission. Methods: At baseline, patients with IBD in clinical remission underwent ileocolonoscopy with assessment of intestinal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity, as well as barrier healing, was prospectively assessed along established scores. During subsequent follow-up, patients were closely monitored for clinical disease activity and the occurrence of major adverse outcomes (MAOs): disease flares, IBD-related hospitalization or surgery, and initiation or dose escalation of systemic steroids, immunosuppressants, small molecules, or biological therapy. Results: The final analysis included 181 patients, 100 with Crohn's disease [CD] and 81 with ulcerative colitis (UC). During a mean follow-up of 35 (CD) and 25 (UC) months, 73% of patients with CD and 69% of patients with UC experienced at least 1 MAO. The probability of MAO-free survival was significantly higher in patients with IBD with endoscopic remission compared with endoscopically active disease. In addition, histologic remission predicted MAO-free survival in patients with UC but not CD. Barrier healing on endomicroscopy was superior to endoscopic and histologic remission for predicting MAO-free survival in both UC and CD. Conclusions: Barrier healing is associated with decreased risk of disease progression in patients with clinically remittent IBD, with superior predictive performance compared with endoscopic and histologic remission. Analysis of barrier function might be considered as a future treatment target in clinical trials. ClinicalTrials.gov number, NCT05157750.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Confocal Laser Endomicroscopy; Endoscopy; Histology; Inflammatory Bowel Diseases; Intestinal Barrier

Multiscale Bowel Sound Event Spotting in Highly Imbalanced Wearable Monitoring Data: Algorithm Development and Validation Study. - Baronetto, Annalisa; Graf, Luisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (JMIR AI, 2024)
BACKGROUND: Abdominal auscultation (i.e., listening to bowel sounds (BSs)) can be used to analyze digestion. An automated retrieval of BS would be beneficial to assess gastrointestinal disorders noninvasively. OBJECTIVE: This study aims to develop a multiscale spotting model to detect BSs in continuous audio data from a wearable monitoring system. METHODS: We designed a spotting model based on the Efficient-U-Net (EffUNet) architecture to analyze 10-second audio segments at a time and spot BSs with a temporal resolution of 25 ms. Evaluation data were collected across different digestive phases from 18 healthy participants and 9 patients with inflammatory bowel disease (IBD). Audio data were recorded in a daytime setting with a smart T-Shirt that embeds digital microphones. The data set was annotated by independent raters with substantial agreement (Cohen κ between 0.70 and 0.75), resulting in 136 hours of labeled data. In total, 11,482 BSs were analyzed, with a BS duration ranging between 18 ms and 6.3 seconds. The share of BSs in the data set (BS ratio) was 0.0089. We analyzed the performance depending on noise level, BS duration, and BS event rate. We also report spotting timing errors. RESULTS: Leave-one-participant-out cross-validation of BS event spotting yielded a median F1-score of 0.73 for both healthy volunteers and patients with IBD. EffUNet detected BSs under different noise conditions with 0.73 recall and 0.72 precision. In particular, for a signal-to-noise ratio over 4 dB, more than 83% of BSs were recognized, with precision of 0.77 or more. EffUNet recall dropped below 0.60 for BS duration of 1.5 seconds or less. At a BS ratio greater than 0.05, the precision of our model was over 0.83. For both healthy participants and patients with IBD, insertion and deletion timing errors were the largest, with a total of 15.54 minutes of insertion errors and 13.08 minutes of deletion errors over the total audio data set. On our data set, EffUNet outperformed existing BS spotting models that provide similar temporal resolution. CONCLUSIONS: The EffUNet spotter is robust against background noise and can retrieve BSs with varying duration. EffUNet outperforms previous BS detection approaches in unmodified audio data, containing highly sparse BS events.
EVALuna2:590878

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Reverse switching from the biosimilar SB2 to the originator infliximab in previously switched patients with inflammatory bowel diseases: results of a prospective long-term cohort study - Fischer, Sarah; Donhauser, Moritz; Cohnen, Sarah Ellen; Fietkau, Konstantin; Vetter, Marcel; Grübel-Liehr, Maria; Dietrich, Peter; Rath, Timo; Wilfer, Angelika; Sologub, Ludmilla; Krebs, Sabine; Dörje, Frank; et al. (Therapeutic Advances in Gastroenterology, 2024)
A clinical study investigating the interchangeability between infliximab, a previously patented biotechnological produced drug (biological) and its successor product biosimilar SB2, which is highly similar to the existing reference product, in the treatment of patients with inflammatory bowel diseases Why was the study done? Biological drugs (like infliximab) are produced using various methods under the involvement of biotechnology. In contrary to generic drugs, due to their complex structure, biosimilars are not exactly the same molecule as the original substance. After the introduction of biosimilars, which are mostly less expensive than the original product, concerns were raised regarding the interchangeability of these substances. This study was conducted to investigate potential changes in efficacy and safety after multiple, so called switches (from the original product to its biosimilar and back). What did the researchers do? The research team switched a group of 95 patients diagnosed with inflammatory bowel disease and therefore treated with the original biologic drug infliximab to the biosimilar SB2, reverse switched them back to the original drug after 96 weeks and observed the patients for another 48 weeks. During the observational phase the disease activity, drug levels and potential side effects were monitored. What did the researchers find? The initial and the reverse switch had no relevant impact on the course of disease and additionally no safety issues occurred. During the 48 weeks observational period, 14.7% of patients discontinued therapy, which was not out of the expected range. Most potential side effects were not considered to be therapy-associated and only 4 of 95 patients discontinued treatment due to safety concerns. The drug levels remained stable during the switches. What do the findings mean? In this study, the research team found no impact of multiple switches on the disease activity in inflammatory bowel disease patients and moreover no safety issues. These findings support the practice of switching between the biologic originator substance infliximab and its biosimilar

Risk factors associated with complications of palliative drainage of ascites with tunneled peritoneal catheters - Machnik, Domenique; Fischer, Sarah; Vetter, Marcel; Lamprecht-Bailer, Ricarda; Rouse-Merkel, Rachel; Klett, Daniel; Neurath, Markus; Strobel, Deike; Zundler, Sebastian; Haberkamp, Sophie (Therapeutic Advances in Gastroenterology, 2025)
Background: Medically intractable ascites causes substantial distress in patients with palliative disease. Tunneled peritoneal catheters have been established as a feasible treatment option allowing patient-controlled paracentesis in a homecare setting. However, while a range of complications is associated with these drainages, risk factors for complications have not been identified so far. Objectives: To explore potential risk factors associated with complications of tunneled peritoneal catheters. Design: Retrospective observational cohort study. Methods: Single-center cohort comprising 49 patients with palliative disease receiving 57 tunneled peritoneal catheters at a tertiary care hospital. Results: Catheter placement was successful in all patients and associated with low numbers of severe complications. Our data suggest a higher risk for severe late complications in patients with benign disease, with drainage replacement, and when performed by less experienced physicians. Conclusion: Tunneled peritoneal catheters are an effective and safe option to treat symptomatic ascites in patients with end-stage palliative disease. The indication should be carefully considered in patients with benign disease and after removal or dislocation of a previous catheter.
CRIS-Team Scopus Importer:2025-01-31
Keywords: ascites; palliative care; peritoneal carcinomatosis; tunneled peritoneal catheter

Segment-Based Spotting of Bowel Sounds Using Pretrained Models in Continuous Data Streams - Baronetto, Annalisa; Graf, Luisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (IEEE journal of biomedical and health informatics, 2023)
We analyse pretrained and non-pretrained deep neural models to detect 10-seconds Bowel Sounds (BS) audio segments in continuous audio data streams. The models include MobileNet, EfficientNet, and Distilled Transformer architectures. Models were initially trained on AudioSet and then transferred and evaluated on 84 hours of labelled audio data of eighteen healthy participants. Evaluation data was recorded in a semi-naturalistic daytime setting including movement and background noise using a smart shirt with embedded microphones. The collected dataset was annotated for individual BS events by two independent raters with substantial agreement (Cohen's Kappa κ =0.74). Leave-One-Participant-Out cross-validation for detecting 10-second BS audio segments, i.e. segment-based BS spotting, yielded a best F1 score of 73% and 67%, with and without transfer learning respectively. The best model for segment-based BS spotting was EfficientNet-B2 with an attention module. Our results show that pretrained models could improve F1 score up to 26%, in particular, increasing robustness against background noise. Our segment-based BS spotting approach reduces the amount of audio data to be reviewed by experts from 84 h to 11 h, thus by 87%.
CRIS-Team Scopus Importer:2023-06-02
Keywords: audio tagging; Bowel sound detection; Convolution; Data models; deep learning; Feature extraction; Neural networks; Recording; Training; transfer learning; Transfer learning

Treatment trajectories and outcomes in inflammatory bowel disease: a tertiary single-centre experience - Wagner, Kim; Müller, Tanja; Vitali, Francesco; Fischer, Sarah; Haberkamp, Sophie; Rouse-Merkel, Rachel; Atreya, Raja; Neurath, Markus; Zundler, Sebastian (Therapeutic Advances in Gastroenterology, 2024)
Background: There is an increasing diversification in the treatment landscape for inflammatory bowel diseases (IBD) leading to therapeutic challenges that can only incompletely be covered by prospective randomized double-blind trials. Real-world observations are therefore an important tool to provide insights into therapeutic strategies. Objectives: To describe the real-world treatment algorithms in an IBD referral centre. Design: Single-centre retrospective cohort study. Methods: We retrospectively analysed prospectively collected data on treatment sequences and outcomes from 502 patients with Crohn’s disease (CD) and ulcerative colitis (UC) treated with infliximab, adalimumab, vedolizumab or ustekinumab at a large German tertiary referral centre. Results: Treatment decisions correlated to baseline patient characteristics. Over time, infliximab continued to be the preferred first-line option in CD and UC, although ustekinumab and vedolizumab, respectively, became increasingly important choices. Remission rates decreased with the advancement of therapy lines. Conclusion: We provide insights into the evolution of tertiary centre real-world treatment sequences that might – together with other observations – help to guide the selection of therapies in IBD. Our data also strongly underscore the unmet need for biomarkers supporting treatment decisions. Trial registration: None.
CRIS-Team Scopus Importer:2024-10-18
Keywords: biological therapy; Crohn’s disease; inflammatory bowel disease; real-world study; treatment algorithms; ulcerative colitis

Update zur Pathophysiologie, Prädiktion und Prävention chronisch-entzündlicher Darmerkrankungen - Fischer, Sarah; Neurath, Markus (Innere Medizin, 2025)
Background: The pathophysiology of inflammatory bowel diseases is not fully understood. In a staged model by the European Crohn’s and Colitis Organization (ECCO) regarding disease development, it is assumed that there is a population at risk for manifestation of disease following subtle changes over time. Objective: This work aims to summarize the current state of knowledge regarding the pathophysiology, prediction and prevention of chronic inflammatory bowel diseases. Materials and Methods: Selective literature research via PubMed. Results: Several genetic, biochemical, and microbiome scores have the potential to identify individuals at increased risk of developing inflammatory bowel disease, possibly up to a decade before onset. Discussion: The growing knowledge regarding the pathogenesis of inflammatory bowel diseases makes prediction before disease onset a possible future diagnostic goal. Hypothetically, early changes before the disease manifests could be reversible and may be amenable to prevention programs.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Environmental factors; Genetic factors; Inflammatory bowel diseases/risk factors; Intestinal barrier; Microbiome